2005
DOI: 10.1007/s00423-004-0532-5
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic hernia repair?TAPP or/and TEP?

Abstract: Randomised trials comparing both methods of hernia repair are lacking. Seven non-randomised studies showed no differences in recurrence rate and morbidity. In general the learning curve for is shorter in favour of TAPP repair.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
32
0
5

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(38 citation statements)
references
References 50 publications
1
32
0
5
Order By: Relevance
“…Endoscopic TEP repair tends to be superior to TAPP repair, because of less morbidity as well as lower recurrence rates and complications [48,49].…”
Section: Discussionmentioning
confidence: 99%
“…Endoscopic TEP repair tends to be superior to TAPP repair, because of less morbidity as well as lower recurrence rates and complications [48,49].…”
Section: Discussionmentioning
confidence: 99%
“…Several laparoscopic techniques have been described to manage groin hernias [4][5][6][7]. Of various endoscopic hernia repair procedures, transabdominal preperitoneal repair (TAPP) [8] and totally extraperitoneal (TEP) [9] repair have been selected for routine use [10]. There are numerous indications for both procedures, whereby the TAPP approach has also been advocated for recurrent and complicated hernias (sliding or incarcerated inguinal hernias) [10].…”
mentioning
confidence: 99%
“…Only one study to date has compared TEP to TAPP repairs, and this study favors the TAPP repair for its ease of performance. This study, however, was based on a review of current literature and not on a trial [8]. A recent large randomized trial demonstrated that laparoscopic repairs had minimal impact on postoperative pain and convalescence, but included recurrent and bilateral repairs, again without blinding [6].…”
mentioning
confidence: 99%